Visual literacy and Socratic seminars in a secondary Montessori classroom - Miller, Kent (My University, 2015)
Often the Arts are marginalized by academia as a bonus event if we have extra time or money. This project is here to prove that the Arts, specifically the Visual Arts have a place in an academic setting and have a valid place among other subjects in the Montessori Philosophy. Being visually literate is as complicated as learning any other form of literacy, but if done correctly, it has the power to improve students' critical thinking skills, observation skills, and their ability to understand complex concepts. This action research will look at 6-8 graders at a public middle school in a large urban area in the upper Midwest. The method of research will involve student surveys, classroom and student artifacts, and observations of Socratic seminars. This study found that by involving students in multiple scaffolding activities, they improved in their ability to become visually literate. Also, by including the students in multiple seminars, their proficiency in visual literacy increased. This method of Non-Traditional Socratic seminars with the use of scaffold activities outlines a frame work for implementing visual literacy content into the main stream of Secondary Montessori Education.
Plan B Paper. 2015. Master of Science in Education- Montessori--University of Wisconsin-River Falls. Teacher Education Department. 48 leaves. Includes bibliographical references (leaves 28-29).
Keywords: Visual literacy; Visual learning; Montessori method of education; Cognition in children